Performance Audit on National Skill Development Fund and National Skill Development Corporation (2008-2014) - CAG of India (CAG of India)
This performance audit report covering the period from 2008-09 to 2013-14, contains the results of the audit of the governance mechanism and activities of National Skill Development Fund and National Skill Development Corporation.
For the Period 2008-2014